Vibrational excitation of the H2X1Σg+ state via electron-impact excitation and radiative cascade. (25th February 2019) - Scarlett, Liam H; Tapley, Jonathan K; Savage, Jeremy S; Fursa, Dmitry V; Zammit, Mark C; Bray, Igor
Abstract: Vibrational excitations of H 2 ( X 1 Σ g +, v i = 0 − 14 ) are investigated via the electron-impact excitation of the B 1 Σ u +, C 1 Π u, B ′ 1 Σ u +, D 1 Π u, and E, F 1 Σ g + states followed by radiative cascade to the vibrational bound and free (continuum) levels of the electronic ground state. The adiabatic-nuclei convergent close-coupling formalism is utilized to calculate cross sections from threshold to 500 eV. Results are in qualitative agreement with previous calculations, however absolute values differ significantly.